Essays on uncertainty and productivity : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Finance, School of Accountancy, Economics and Finance, Massey University, Auckland, New Zealand - Dang, Tam Hoang Nhat (Massey University, 2026)
Uncertainty has become a defining characteristic of the global economy, shaping both macroeconomic performance and firm-level behavior. Recent crises such as the Global Financial Crisis, the COVID-19 pandemic, and the Russo-Ukrainian war have highlighted how shocks transmit across markets through energy and financial linkages, disrupting stability and growth. Understanding the multifaceted dimensions of uncertainty and its interaction with real and financial activities is therefore essential for evaluating global economic resilience. This thesis investigates these dimensions through three interrelated essays combining macro-sectoral, energy, and financial perspectives. Essay One examines the structure and evolution of expected uncertainty spillovers across emerging market sectors using a quantile time-frequency connectedness framework, uncovering heterogeneous interdependencies across time horizons and market conditions. Essay Two assesses how the global geopolitical-energy uncertainty (GEU) influences firm-level productivity, offering new insights into the productivity effects of intertwined geopolitical and energy shocks. Essay Three analyzes how cross-listing in US markets affects the productivity of energy-sector firms during the last two decades characterized by rising uncertainty.
Listed in 2026 Dean's List of Exceptional Theses
Keywords: Uncertainty; Economic aspects; Developing countries; Economic conditions; Industrial productivity; Econometric models; Energy industries; Capital productivity; Dean's List of Exceptional Theses; 380107 Financial economics